2021
DOI: 10.1111/ocr.12545
|View full text |Cite
|
Sign up to set email alerts
|

Does quality of orthodontic treatment outcome influence post‐treatment stability? A retrospective study investigating short‐term stability 2 years after orthodontic treatment with fixed appliances and in the presence of fixed retainers

Abstract: Objective: The present study aimed to evaluate stability 2 years after orthodontic treatment and to investigate the influence of various pre-treatment and posttreatment prognostic factors on stability.Setting and Sample Population.Consecutive patients treated with full fixed appliance and retained with fixed retainers were retrospectively assessed for eligibility. Materials and Methods: Digital models were analysed at treatment start (T0), end of treatment (T1) and 2 years post-treatment (T2). The Peer Assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Pancherz sieht in einer stabilen posttherapeutischen Interkuspidation den Schlüssel zu einem stabilen Behandlungsergebnis [5]. Ein objektiv gutes kieferorthopädisches Therapieresultat stellt auch nach Gera et al ein Stabilitätskriterium dar [44]. Bezüglich der Stabilität post Therapie mit dem Herbstscharnier muss beachtet werden, dass nach einer Retentionsphase die skelettalen Effekte langfristig kaum noch nachweisbar sind, die Okklusion jedoch relativ stabil bleibt [11].…”
Section: Stabilitätunclassified
“…Pancherz sieht in einer stabilen posttherapeutischen Interkuspidation den Schlüssel zu einem stabilen Behandlungsergebnis [5]. Ein objektiv gutes kieferorthopädisches Therapieresultat stellt auch nach Gera et al ein Stabilitätskriterium dar [44]. Bezüglich der Stabilität post Therapie mit dem Herbstscharnier muss beachtet werden, dass nach einer Retentionsphase die skelettalen Effekte langfristig kaum noch nachweisbar sind, die Okklusion jedoch relativ stabil bleibt [11].…”
Section: Stabilitätunclassified
“…However, differences in lower incisor inclination were statistically significant. Gera et al [36] conducted a retrospective study and found that stability was good two years after orthodontic treatment, with less than 2% experiencing undesirable changes. Dalya Al-Moghrabi et al [1] found that fixed retainers were more effective than vacuum-formed retainers in maintaining mandibular anterior segment alignment at a 4-year follow-up.…”
Section: Bonded Retainers Versus Removable Retention Devicesmentioning
confidence: 99%
“…On the other hand, it has been shown by some authors that long-term stability is correlated to the quality of the orthodontic treatment outcome [13,14]. If the quality of treatment outcome is indeed influencing the long-term stability favorably, it would be of interest to study a sample selected for its high-quality end-of-treatment outcome as it will likely evolve differently in time compared to an average sample.…”
Section: Introductionmentioning
confidence: 99%